Redução de danos em crises induzidas por psicodélicos: uma leitura junguiana - Beserra, Fernando Rocha (2022)
The research was focused on supporting young people in crisis induced by psychedelic substance carried out in harm reduction actions in the context of electronic music parties. The research question aimed at verifying whether the acceptance of crisis induced by psychedelics by harm reduction workers favor feelings of security and reassurance for the user. A total of 10 young adults of both sexes and aged between 18 and 27 years old participated in the research. The mixed method was used in the research, with a qualitative predominance. The instruments Challenging Experience Questionnaire, WHOQOL-Bref, ASSIST and a research protocol were applied. Data were systematized and later analyzed using the IBM SPSS program and analysis of correlations between variables was performed using the non-parametric method. In the qualitative scope, semi-structured interviews were carried out with 8 participants. The information was systematized through coding. Subsequently, the speeches were interpreted and discussed through analytical psychology and post-Jungian authors and references in the field of harm reduction. The main objective was to investigate the harm reduction related to the consumption of psychedelics through a support protocol and responses to care in crisis induced by psychedelic substances in the context of electronic music parties. For this purpose, quantitative objectives were established, which investigated: the quality of life; the intensity of the factors of a psychedelic-induced crisis; the profile of psychoactive substance use; self-care; the form and meaning of the use of psychedelic substances and the correlations between different variables were analyzed. Among the qualitative objectives, it was aimed to investigate: the reaction of people after a crisis; the participants´s report related to the experience in the assistance from the harm reduction staff; the expressed attitudes and the mode of consumption of psychedelic substances. It was also proposed to build a product through a support protocol for psychedelic-induced crises (PROSC) for harm reduction actions. The quantitative results indicated, in the researched group, that the lower the self-care with the use of alcohol and food, the more intense are the experiences of fear, complaints and physical stress during the use of psychedelics, and that the more likely the use when you are sad, more intense tend to be the experiences of fear, complaint, and physical stress. Qualitatively, it was identified that the crises resulting from the use of psychedelics involved fear, physical stress, fear of madness and death, feeling of persecution and rejection, altered bodily sensations, displeasure and strange feeling, in addition to the need for support and seeking help among peers, at the medical center and in harm reduction. During the crises, dynamics of regression, dissociation, compensation and use of defense mechanisms were observed. The issue raised, that the support could boost security and reassurance of user was endorsed by the information obtained within the researched group and context, without the possibility of generalization